Bioactivity of leaf and bark extractives of Prosopis africana (Guill., Perrott. and Rich.) Taub. against some multidrug-resistant microbes (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
The aqueous, methanolic, ethanolic and n-Hexane leaf and bark of P. africana extracts were tested for antimicrobial activity against five clinical pathogens: Acinetobacter baumanii, Escherichia coli 25922, Escherichia coli ESBL, Methicillin-Resistant Staphylococcus aureus, and Candida albicans ELI. Antimicrobial sensitivity test was carried out using the agar well diffusion method at a stock and varying concentrations of 500, 1000 and 1500 mg/mL. Results indicated that n-hexane leaf and bark extracts could not inhibit the organisms. Aqueous leaf extracts inhibited A. baumanii, MRSA, E. coli ESBL and E. coli 25922, while aqueous bark extract inhibited A. baumanii, MRSA, E. coli 25922, C. albicans ELI. Methanolic leaf extracts inhibited A. baumanii, MRSA, E. coli ESBL, while Methanolic bark extracts inhibited A. baumanii, MRSA, E. coli ESBL, E. coli 25922, C. albicans ELI. Ethanolic bark extracts inhibited A. baumanii, MRSA, E. coli ESBL, E. coli 25922, C. albicans ELI. The Minimum Inhibitory Concentration of the extracts for leaf and bark ranged from 1500 mg/mL – 23.43 mg/mL. Minimum Bactericidal Concentration was observed in aqueous leaf extracts against E. coli 25922 at 1500 concentration. Antibiotics susceptibility test indicated multidrug resistance by the test organisms with only Ofloxacin, Gentamycin, Ceftazidime and Nitrofurantoin eliciting inhibitory activity against A. baumanii, E. coli ESBL and E. coli 25922, respectively. Preliminary phytochemical screening revealed that P. africana leaf and bark extractives contained beneficial phytochemicals responsible for their high bioactivity against the selected clinical isolates.